The effects of chronic melatonin treatment on myocardial function and ischaemia and reperfusion injury in a rat model of diet-induced obesity - Nduhirabandi, Frederic (Stellenbosch : Stellenbosch University, 2010)
Thesis (MScMedSc)--University of Stellenbosch, 2010.